La literatura catalana entre el barroc i el romanticisme - Albert Rossich (Caplletra: Revista Internacional de Filologia, 2015)
The author considers methodological dificulties of many kinds that the study of Catalan literature presents between Baroque and Romanticism; reviews postulates and conclusions of Catalan literary historiography and defines the extent of general reference frameworks, for instance "rococó", locating the discussion in the field of interrelations between literature and the process of linguistic substitution.